Analysis of the force-velocity Profile in female Ballet dancers - Escobar Álvarez, J.A.; Reyes, P.J.; Pérez Sousa, M.Á.; Conceição, F.; Fuentes García, J.P. (Journal of Dance Medicine & Science, 2020)
Jumping ability has been identified as one of the best predictors of dance performance. The latest findings in strength and conditioning research suggest that the relationship between force and velocity mechanical capabilities, known as the force-velocity profile, is a relevant parameter for the assessment of jumping ability. In addition, previous investigations have suggested the existence of an optimal force-velocity profile for each individual that maximizes jump performance. Given the abundance of ballistic actions in ballet (e.g., jumps and changes of direction), quantification of the mechanical variables of the force-velocity profile could be beneficial for dancers as a guide to specific training regimens that can result in improvement of either maximal force or velocity capabilities. The aim of this study was to compare the mechanical variables of the force-velocity profile during jumping in different company ranks of ballet dancers. Eighty-seven female professional ballet dancers (age: 18.94 ± 1.32 years; height: 164.41 ± 8.20 cm; weight: 56.3 ± 5.86 kg) showed high force deficits (> 40%) or low force deficits (10% to 40%) regardless of their company rank. Our results suggest that dance training mainly develops velocity capabilities, and due to the high number of dramatic elevations that dance performance requires, supplemental individualized force training may be beneficial for dancers. The individualization of training programs addressed to the direction of each individuals imbalance (high force or low force) could help dancers and their teachers to improve jump height and therefore dance performance.